Pelaksanaan Wajib Uji Barang Di DKI Jakarta - Koentoro Soebijarso (Jurnal Kimia dan Kemasan, 1976)
In the fraraework of compulsory testing in DK.I JAKARTA several process of collecting and certification of samples has been done, with the purpose to simplify the system of administrative worko To cheek the quality of the product distributed into the market, Balai Penelitian Industri and Dinas Perindustrian DKI conduct market sampling and the result of this is alsoused for standardization feedback.